The Macedonian Labour Market: What makes it so different? - Blazevski, Nikica Mojsoska; Kurtishi, Nedjati (Ревија за социјална политика/Journal of Social Policy, 2012)
The aim of this paper is to investigate the performance of the Macedonianlabour market in the period 2006-2011, as well as to provide a comparative analysis with the countries from the region and the EU. In particular, for over a decade, Macedonian labor market puzzles economic researchers. Despite the expected improvement in the allocative efficiency of the markets (including labour market)in the process of transition to a market economy, the performance of the Macedonian labour market has deteriorated during the transition. Unemployment rate for the population aged 15-64 reached 37.7% in 2005, though it has been declining modestly since then to 31.6% in 2011. Participation and employment rates of 64.2% and 43.9%, respectively, are low compared to the peer countries form the region, and even more if compared to the EU countries. This holds even more so for Macedonian females. In this regard, the paper examines the main challenges in the labour market, in general, but also does so for specific groups of workers (differentiated by age, gender анд education). We also calculate the extent of the skill match, as well as the presence of the over/under-education phenomenon(mismatches). Moreover, it empirically tests the determinants of the employment, that is which factors might bring higher employment rates.